The great frozen sea [electronic resource] : a personal narrative of the voyage of the "Alert" during the Arctic expedition of 1875-6 - Markham, Albert Hastings, Sir, 1841-1918 (London : Daldy, Isbister, 1878)
Also available in French. See CIHM microfiche no. 04665. "'There's a flag on the mast .'" Includes index. Electronic reproduction. Mode of access: Internet. 44